Coastal Nutrition Status of the Country Reviewed from Social Culture and Islamic Perspective - Eliska Eliska; Nurhayati Nurhayati; Petti Sitti Fatimah (Universitas Teuku Umar, 2020)
Coastal communities are people who live and carry out socio-economic activities that depend on coastal resources, one of which is fishermen. The cultural identity of coastal communities as a whole is formed from the culture of fishermen who are directly related to the management of coastal and marine resources. Nutritional problems arise not only from health problems but also influenced by social culture and religion. The design of this study uses quantitative research with a Cross Sectional.The sample is the total population selected by the purposive sampling method, which is 71 students from five schools. The instrument in this study used a questionnaire. Techniques and data processing are carried out by using a computer program to present data in the form of frequency and then the results are presented in the table. It is known that there is a relationship between nutritional status and socio-culture in coastal communities because the nutritional status of school-age children is below the threshold of 25.4%, and 12.7% is very thin. This happens because most parents of students have daily work as fishermen so that the lack of income from parents causes children's nutritional intake to decrease, while seen from the cultural tribes of the coastal community there are more Javanese tribes which result in low nutritional status due to lack of variety in food intake.